Genetic conservation of hlyA determinants and serological conservation of HlyA: basis for developing a broadly cross-reactive subunit Escherichia coli alpha-hemolysin vaccine. - O'Hanley, P (1993)
The HlyA determinant among Escherichia coli isolates from patients with symptomatic urinary tract infection was compared in this report with a prototype HlyA encoded by pSF4000 by DNA-DNA hybridization tests with 20-base synthetic oligonucleotides and monoclonal antibody binding and neutralization assays. Hybridization results demonstrated that 349 (98%) of 357 definitive reactions among 54 hemolytic strains shared homology with seven DNA probes spanning many HlyA regions corresponding to residues (R) 41 to 47, 55 to 61, 248 to 254, 306 to 312, 336 to 343, 402 to 408, and 929 to 935. Genetic divergence was identified by lack of hybridization signals among 17 to 76% of the hemolytic strains within the distal portion of a predicted hydrophobic region corresponding to R491 to 319 and within a predicted hydrophilic region corresponding to R491 to 497 and R532 to 538. Serological studies demonstrated that 26 (81%) culture supernatants of 32 hemolytic strains were bound by all 12 monoclonal anti-HlyA antibodies. Among five of six remaining strains, the culture supernatants were bound by 3 to 11 monoclonal antibody preparations. There was only one hemolytic culture supernatant that failed to be bound by any monoclonal antibody, although the strain hybridized with nine hemolysin DNA probes. In addition, hemolytic activity of all 24 different culture supernatants tested was reduced by at least twofold by one monoclonal antibody specific for R2-161. These data extend and support previous views that the HlyA determinant is conserved among E. coli strains and suggest that a broadly cross-reactive HlyA subunit vaccine can be developed.